2007
DOI: 10.1021/ol0630853
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Nucleotidylyltransferases To Prepare Sugar Nucleotides

Abstract: [reaction: see text] Enzymatic approaches to prepare sugar nucleotides are gaining in importance and offer several advantages over chemical synthesis including high yields and stereospecificity. We report the cloning, expression, and purification of two new wild-type thymidylyltransferases and observed catalysis with a wide variety of substrates. Significant product inhibition was not observed with the enzymes studied over a 24 h period, enabling the efficient preparation of 15 sugar nucleotides, clearly demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 35 publications
3
79
0
Order By: Relevance
“…PEPs was overexpressed and purified using standard methods for His 6 -tagged proteins as previously described (Timmons et al 2007;Jakeman et al 2008) with the following modifications. Protein overexpression was induced with 1 mM IPTG, followed by incubation at 17˚C overnight.…”
Section: Expression and Purification Of Pepsmentioning
confidence: 99%
“…PEPs was overexpressed and purified using standard methods for His 6 -tagged proteins as previously described (Timmons et al 2007;Jakeman et al 2008) with the following modifications. Protein overexpression was induced with 1 mM IPTG, followed by incubation at 17˚C overnight.…”
Section: Expression and Purification Of Pepsmentioning
confidence: 99%
“…Compounds 9 and 11 were first evaluated as Glc-1-P (1) analogue substrates for Cps2L given that the enzyme had previously demonstrated a broad substrate specificity, 34,37,38 including poor conversion (3−10%) observed for β-L-fucosyl phosphate. 34 Negligible turnover (<1%) to sugar nucleotide products were observed by HPLC over 24 h using 2−10 EU of Cps2L with a 8:1 ratio of 9 or 11 relative to dTTP substrate (2) (Supporting Information). This suggested that the L-rhamnose phosphonates did not act as substrates for Cps2L.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 The recent observation that the glycosyltransferase VinC is capable of processing both a-and b-anomer of a sugar nucleotide to give glycosylated products with corresponding inversion of stereochemistry at the anomeric linkage 13 underlies the importance of stereospecific synthetic methods for the preparation of these substrates. Although the enzymatic preparation of these compounds has emerged, [14][15][16][17][18] the versatility available via chemical synthesis is unparalleled.…”
Section: Introductionmentioning
confidence: 99%